Using ski industry response to climatic variability to assess climate change risk: An analogue study in Eastern Canada. (February 2017) - Rutty, Michelle; Scott, Daniel; Johnson, Peter; Pons, Marc; Steiger, Robert; Vilella, Marc
Abstract: To accurately characterize the ski industry's risk to future climate change and varied quality of snow conditions, it is important to assess how the industry has managed and adapted to contemporary anomalously warm ski seasons. This is the first temporal climate change analogue study to use higher resolution daily performance data at the individual ski area scale, including reported snow quality, ski lift operations, slope openings, and water usage for snowmaking. The record warm winter of 2011–2012 in the Ontario ski tourism market (Eastern Canada) is representative of projected future average winter conditions under a mid-century, high greenhouse gas emissions scenario (RCP 8.5), which was compared to the 2010–2011 season which was climatically normal (for the 1981–2010 period). Supply-side impacts across the 17 ski areas during the analogue winter included a total average decrease in the ski season length (−17% days), operating ski lifts (−3%), skiable terrain (−9%), reduced snow quality (e.g., -46% days with packed powder), snowmaking days (−18%), and an increase in water usage for snowmaking (e.g.,  +300% in December). Demand-side impacts include a 10% decrease in overall skier visits, with a resort size-correlation (small −20%, intermediate −14%, large −8%). With reduced operational ski terrain and more frequent marginal snow conditions, visitor experience is adversely affected more frequently. Collectively, these findings identify differential impacts in the ski tourism market and can assist ski area managers, communities, investors and governments with developing climate change adaptation plans. Highlights: The impact of climate change analogue conditions on ski operations is broader than reported in previous studies. Ski operations under anomalously warm temperatures are not binary, but a continuum of partial capacity. Differential vulnerabilities are recorded by ski resort size (i.e., small, intermediate and large resorts) and month. Ski demand is less sensitive to record warm conditions than supply-side operations.